2004
DOI: 10.1111/j.1529-8817.2004.03078.x
|View full text |Cite
|
Sign up to set email alerts
|

MOLECULAR CHARACTERIZATION OF THE ASSIMILATORY NITRATE REDUCTASE GENE AND ITS EXPRESSION IN THE MARINE GREEN ALGA DUNALIELLA TERTIOLECTA (CHLOROPHYCEAE)1

Abstract: Nitrate is used as a nutrient for growth by many organisms through the nitrate assimilation pathway. The key enzyme involved in nitrate assimilation is nitrate reductase (NR). Transcriptional regulation of NR genes has been studied in various phototrophic eukaryotes from freshwater or terrestrial habitats. Here, we describe the first NR gene from a marine phytoplankton, the green alga Dunaliella tertiolecta Butcher. Its sequence is very similar to that of the other green algae, but its intron structure and tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 40 publications
6
48
1
Order By: Relevance
“…They have substantial similarity, particularly within functional domains, but present large variation in GC content at the third codon position and in the number of introns. NR genes from green algae have 18 introns in Chlorella vulgaris (Dawson et al 1996), 15 in Chlamydomonas reinhardtii (Merchant et al 2007), ten in Volvox carteri (Gruber et al 1992), and also Dunaliella tertiolecta showed two introns in a partial region of the gene cloned (Song and Ward 2004). The intron positions are different between fungi and plants, but conserved within these groups (Zhou and Kleinhofs 1996).…”
Section: Introductionmentioning
confidence: 95%
“…They have substantial similarity, particularly within functional domains, but present large variation in GC content at the third codon position and in the number of introns. NR genes from green algae have 18 introns in Chlorella vulgaris (Dawson et al 1996), 15 in Chlamydomonas reinhardtii (Merchant et al 2007), ten in Volvox carteri (Gruber et al 1992), and also Dunaliella tertiolecta showed two introns in a partial region of the gene cloned (Song and Ward 2004). The intron positions are different between fungi and plants, but conserved within these groups (Zhou and Kleinhofs 1996).…”
Section: Introductionmentioning
confidence: 95%
“…Although transcription of NR can be induced by the presence of nitrate alone in eukaryotes (Song and Ward, 2004;Poulsen and Krö ger, 2005), the lower Fv/Fm ratio was possibly due to insufficient N (Tolonen et al, 2006) for the dominant phytoplankton in chlorophyll a measurements, which at that time were eukaryotic phytoplankton. Similar to Prochlorococcus, eukaryotic phytoplankton downregulated rbcL genes in the Fe treatment, especially two Chrysophytes, Epipyxis pulchra and Ochromonas aestuarti, and two Prymnesiophytes, Chrysochromulina alifera and Chrysochromulina flava (Figure 5d).…”
Section: Relief From Fe Limitation In Oligotrophic Taxamentioning
confidence: 99%
“…Analysis of NR genes showed that gene expression in higher plants and algae was regulated primarily at the transcriptional level. Song and Ward (2004) found a different transcriptional response of NR in the marine alga D. tertiolecta compared to that found in studies with freshwater green algae such as Chlamydomonas reinhardtii, V. carteri, and Chlorella vulgaris (Quesada and Fernandez 1994;Cannons and Pendleton 1994). In the freshwater green algae, NR transcription is induced by the removal of repressors such as ammonia and metabolites of ammonia and under N-depleted conditions.…”
Section: Introductionmentioning
confidence: 64%
“…During the last two decades, genes encoding NR have been cloned from several algae such as Chlamydomonas reinhardtii , Volvox carteri (Gruber et al 1992), Chlorella vulgaris (Dawson et al 1996), Dunaliella tertiolecta (Song and Ward 2004) and Phaeodactylum triconutum (Allen et al 2005). Moreover, Kindle et al (1989) developed a nuclear transformation system for C. reinhardtii, using micro-projectile bombardment to introduce the C. reinhardtii NR gene ) into a nit1 mutant strain that lacks NR activity.…”
Section: Introductionmentioning
confidence: 99%